2010
DOI: 10.1093/ndt/gfq309
|View full text |Cite
|
Sign up to set email alerts
|

FGF-23 and future cardiovascular events in patients with chronic kidney disease before initiation of dialysis treatment

Abstract: Elevated FGF-23 plasma levels predict cardiovascular events in CKD patients not on dialysis therapy. This finding complements two recent cohort studies in which incident and prevalent haemodialysis patients with highest FGF-23 levels had worst survival. Lowering FGF-23 levels (e.g. by oral phosphate binder medication) could emerge as a promising new therapeutic option to reduce cardiovascular morbidity in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
127
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 27 publications
7
127
2
1
Order By: Relevance
“…If FGF23 is directly correlated to CV and coronary events (29,(45)(46)(47), vascular alterations (48), left ventricular hypertrophy (28,30), and mortality (9,49,50), it seems obvious that a VLpD may be useful to prevent CV events reducing FGF23 levels.…”
Section: Discussionmentioning
confidence: 99%
“…If FGF23 is directly correlated to CV and coronary events (29,(45)(46)(47), vascular alterations (48), left ventricular hypertrophy (28,30), and mortality (9,49,50), it seems obvious that a VLpD may be useful to prevent CV events reducing FGF23 levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the only source of circulating FGF23 in renal disease is the bone [21,31], in spite of the fact that FGF23 transcripts can be detected in liver, heart, ISSN:2155-9880 JCEC, an open access journal Heart Transplantation J Clin Exp Cardiolog brain and thymus. However, with the increasing number of publications demonstrating the involvement of FGF23 in left ventricular dysfunction [12], atrial fibrillation [12] and left ventricular hypertrophy [13] it appears feasible that under pathological conditions secondary sources of FGF23 exist. In order to determine whether cardiomyocytes are able to express FGF23 we stimulated cultures with a variety of growth factors and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in renal function leads to a decreased phosphate excretion which is believed to be compensated through increases in circulating FGF23 by inducing phosphate excretion and negative regulation of vitamin D synthesis. Recent studies demonstrated the association of FGF23 with left ventricular dysfunction [12], atrial fibrillation [12], left ventricular hypertrophy [13] and it might serve as a prognostic marker for all-cause mortality and surviving in stable systolic HF [14,15]. A correlation between Chronic Kidney Disease (CKD) and HF is well recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic and experimental data support FGF23 elevation as a novel risk factor for ESRD, cardiovascular disease, and mortality (2)(3)(4)(5). These findings, along with evidence that FGF23 levels increase with dietary phosphate loading and decrease with restriction (6)(7)(8), have stimulated interest in developing clinical strategies to reduce FGF23 levels in CKD.…”
Section: Introductionmentioning
confidence: 96%